Effect of Supplementation of Different Levels of Egg Yolk on Cryopreservation of Pantja Buck Semen in Tris Dilutor - Rashmi; Kumar, Sunil; Gupta , Harihar Prasad; Prasad, Shiv (The Indian Journal of Animal Reproduction, 2024)
Present study was conducted to determine the optimum concentration of egg yolk in extender for diluting Pantja buck  semen and its effect on post-thaw semen quality. Tris-citric acid-fructose-egg yolk-glycerol (TCF-EY) extender containing  4 different levels (5, 10, 15 and 20%) of egg-yolk was used for cryopreservation. Thirty-two (32) ejaculates were collected  from four (04) bucks (eight ejaculates from each buck). Semen ejaculates after collection were pooled (4 ejaculates = 1  pooled ejaculate) on daily basis and this pooled ejaculate was divided and diluted into four groups as D1[Neat semen +  tris-fructose-citric acid-egg yolk (@5%)-glycerol], D2[Neat semen + tris-fructose-citric acid-egg yolk (@10%)-glycerol],  D3[Neat semen + tris-fructose-citric acid-egg yolk (@15%)-glycerol] and D4[Neat semen + tris-fructose-citric acid-egg  yolk (@20%)-glycerol], and evaluated for physico-morphological parameters (sperm motility, live spermatozoa count,  abnormal spermatozoa percent, plasma membrane integrity and acrosomal integrity) at post-dilution, post-equilibration  and post-thaw stages. Biochemical parameters {Malondialdehyde (MDA), Glutamic Oxaloacetic Transaminase (GOT),  Glutamic Pyruvate Transaminase (GPT) and Glutathione Peroxidase (GSH-Px)}were also estimated before dilution and  at post-thaw stages of semen freezing. Significant difference (P< 0.05) was observed for all the physico-morphological  and biochemical parameters at various stage of semen freezing in various diluters. All seminal parameters except total  sperm abnormality showed higher values in D2 (10% EY) group at post-dilution, post-equilibration and post-thaw stages  compared to other groups. Likewise, significantly lower values for MDA, GOT, GPT and higher value for GSH-Px were  observed in D2 group at post-thaw stage of semen freezing. It was therefore, concluded that 10% egg yolk level (V/V)  supplementation in Tris-citric acid-fructose-egg yolk -glycerol extender provides comparatively better post-thaw semen  quality of Pantja buck semen.
Keywords: Semen; cryopreservation; Pantja buck; egg yolk; tris citrate extender